Sphyrna alleni sp. nov., a new hammerhead shark (Carcharhiniformes, Sphyrnidae) from the Caribbean and the Southwest Atlantic. - Gonzalez, Cindy; Postaire, Bautisse; Driggers, William; Caballero, Susana; Chapman, Demian (Zootaxa, 2024)
Hammerhead sharks (Family Sphyrnidae) comprise a monophyletic Miocene radiation of carcharhiniform sharks characterized by their laterally expanded and dorsoventrally compressed head (‘cephalofoil’). The bonnethead shark (Sphyrna tiburo) is currently described as a single amphi-American hammerhead species composed of the subspecies Sphyrna tiburo tiburo in the Western Atlantic Ocean (WA) and S. tiburo vespertina in the Eastern Pacific Ocean (EP). Variation in mitochondrial DNA and cephalofoil shape suggest a species complex, with S. tiburo occurring in the U.S., Mexico, and Bahamas; S. aff. tiburo occurring from Belize to Brazil; and S. vespertina occurring in the EP. Morphometric, meristic, and genetic variation was used to resolve the bonnethead shark complex in the Western Atlantic. Twenty-three specimens (12 S. aff. tiburo from Belize and 11 S. tiburo from U.S.) were subject to sixty-one morphometric measurements and three meristic characters (counts of the number of precaudal vertebrae, lower and upper rows of functional teeth). An allometric formula was used to standardize any effect caused by differences in size of the individuals and data were analyzed with univariate and multivariate statistics. Sphyrna aff. tiburo and S. tiburo have non-overlapping vertebral counts (80-83 and 71-74 respectively) but no morphometric differences were detected. Although not captured in morphometric analysis, the cephalofoil of S. aff. tiburo has a more pointed anterior margin than S. tiburo that together with lobule shaped posterior margins gives the cephalofoil a distinctive shovel-shaped appearance. Concatenated mitochondrial sequences and 12 nuclear microsatellite markers clearly separated S. aff. tiburo and S. tiburo. We conclude that this complex comprises two species in the Western Atlantic, S. tiburo and S. alleni sp. nov., and we provide a description of the latter, which is distinguished by precaudal vertebral counts (80-83), a shovel-shaped cephalofoil with rounded posterior margins, and robust differences in mitochondrial and nuclear genetic markers. We suggest nuclear genetic and meristic examination of EP bonnetheads is needed to update the taxonomical status and redescribe S. vespertina.